2022
DOI: 10.1016/j.amsu.2021.103230
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal oxygen therapy decrease the risk of mortality and the use of invasive mechanical ventilation in patients with severe SARS-CoV-2 pneumonia? A retrospective and comparative study of 265 cases

Abstract: Introduction Corona virus disease (Covid-19) affects the airways and induces pulmonary lesions, patients with this disease require oxygen therapy as the disease progresses. Several oxygenation options have been used, l’HFNO had showed beneficial effects The objective of this study To evaluate the efficacy of high-flow nasal oxygen HFNO versus non-invasive ventilation in COVID-19. Methods This is a retrospective and comparative study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…After excluding duplicates and evaluating the full texts of articles, we identified 23 eligible studies 9 , 11 32 (3 RCTs, 20 , 24 , 26 8 prospective observational studies, 13 , 16 , 18 , 19 , 22 , 25 , 28 , 30 and 12 retrospective observational studies). 9 , 11 , 12 , 14 , 15 , 17 , 21 , 23 , 27 , 29 , 31 , 32 The process of searching and screening is described in Figure 1 . The main characteristics of the articles included in the meta-analysis are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After excluding duplicates and evaluating the full texts of articles, we identified 23 eligible studies 9 , 11 32 (3 RCTs, 20 , 24 , 26 8 prospective observational studies, 13 , 16 , 18 , 19 , 22 , 25 , 28 , 30 and 12 retrospective observational studies). 9 , 11 , 12 , 14 , 15 , 17 , 21 , 23 , 27 , 29 , 31 , 32 The process of searching and screening is described in Figure 1 . The main characteristics of the articles included in the meta-analysis are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were considered to have an unclear risk of bias. The 20 observational 9 , 11 19 , 21 23 , 25 , 27 32 studies were assessed using the NOS checklist, and the results are shown in the Table 2 . All studies were of medium quality (⩾5 stars) or above, and 10 were considered high quality (⩾8 stars).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have read with great interest this study [ 1 ] that analyzes the impact obtained with the use of nasal high flow oxygen (HFNO) compared with non-invasive ventilation (NIV) for the treatment of patients with COVID-19 and shows a better survival with the use of HFNO. Although the study has a retrospective design, we consider that there are some points that would be better explained.…”
mentioning
confidence: 99%